Comunicação e disputa hegemônica na Venezuela no pós-golpe de abril de 2002 - Simioni, Mônica (2007)
On April 11th 2002, the President of Venezuela Hugo Chávez sustained an unsuccessful coup détat orchestrated through the media by the dominant leading social circles, owner of the country s main communication vehicles, jointly with conservative sectors of the Armed Forces. From the reestablishment of democracy, the government started thinking its communications policy as one of the strategic sectors. Amidst the predominance of capitalism s sole notion according to which socialism was buried along with the fall of the Berlin Wall , the leader of the so-called Bolivarian Revolution is at the head of a process which has been receiving relevant attention in all political fields around the planet. His government questions the neoliberal globalization, carries an anti-imperialist nature and proposes the endogenous development of the nations, transforming society from the economical, cultural and social point of views. One of the biggest oil producers in the world, Venezuela faces a fierce internal and external struggle of ideas. The Revolution has its methods and perspectives questioned by opposers and supporters, in a dialectical process of constructing a new socialism, the 21st Century Socialism. In this process, which, until this stage, is marked by a reform of the bourgeoisie State, the President s leadership has been essential, mainly in response to a deficient political system. The base of its support is the strengthening of participative democracy. This work s hypothesis is that the communications policy adopted by Hugo Chávez Government is one of the political sustainers of the Bolivarian process, where war waged among the favorable and contrary information vehicles is moderated by the biggest international media corporations, reproducers of the great capital interests. Having this in view, we analyze the role of contra-informative media in the dispute for hegemony